The Effectiveness of Hybrid Learning in Improving Students' Academic Writing Skill - Patandingan, M Zainuddin (FKIP Unismuh Makassar, 2025)
The study aimed: 1) To measure the extent of the students' achievement in writing academic papers through Hybrid learning, 2) To analyze the extent of the students' progress in writing academic papers through face to face Learning. 3) To know that using hybrid learning is more effective than using face-to-face instruction in improving students' achievement in writing academic writing. This study used quasi-experimental research. It intended to determine whether there was an influence of using hybrid learning to the quality of students' academic papers. There was a significant enhance in learning outcomes of the students who learned academic writing through Hybrid learning instruction compared to the students who took the learning without Hybrid learning instruction. Learning outcomes of Hybrid learning instruction are shown by the results of a group and an experimental posttest and a control group . It shown a significant result of students taught by using Hybrid learning instruction and those taught not using Hybrid learning instruction, that Hybrid learning was useful in teaching academic writing. .